Landasan Biblical tentang Peneguhan bagi Murid Kristus - Sostenis Nggebu (Tumou Tou, 2023)
The problem discussed in this article is closely related to the importance of establishing for new believers. Establish serves to convince his faith, as well as to remove all obstacles that hinder a person's decision to believe in the Lord Jesus, such as doubts or feeling unworthy before God. The goal is to establish himself in order to grow in his spirituality. The method used is the Bible study method. The results show that establishing of a new convert is a strategic step to solidify his decision to become a follower of Jesus Christ. In addition, edification has a close relationship with evangelism to prepare him to join the local congregation. It is also clear that establishing is not the same as “Sidi” (learn church doctrine or catechism). Because establishing is a place for reaffirmation of his faith before he was handed over to the church. Establishing has a strategic place in building the mature Body of Christ because it strengthens its faith and testimony.